Analytical abilities and the performance of HR professionals - Kryscynski, David; Reeves, Cody; Stice‐Lusvardi, Ryan; Ulrich, Michael; Russell, Grant (Human Resource Management, 2018)
Recent years have shown an increased focus on workforce analytics and the importance of workforce analytics in helping HR professionals to be more useful business partners. This suggests that HR professionals may need to become more and more data savvy and develop better analytical abilities if they hope to perform well and contribute meaningfully in the future. Despite this emphasis, there has been no research explicitly connecting the individual level analytical abilities of HR professionals to their job performance. Using a proprietary sample of 360 feedback surveys from 1,117 HR professionals in 449 unique organizations we test this general relationship. We also test whether the relationship varies by industry‐, company‐, and job‐level factors. We find support for our main hypotheses that HR professionals with higher analytical abilities will also have higher perceived job performance. We also find that the strength of this relationship varies by some job roles. We explore and discuss these empirical results.